Communications on Agricultural Research, Development, and Extension Teams - Donald L. Esslinger; Constance M. McCorkle (Journal of Applied Communications, 1986)
Domestically and internationally, agricultural research, development, and extension (ARD&E) programs are experiencing a resurgent interest in interdisciplinary collaboration as a more effective approach to enhancing farm productivity and human well-being.